Enhanced basal melting in winter and spring: seasonal ice–ocean interactions at the Ekström Ice Shelf, East Antarctica - O. Zeising; T. Hattermann; L. Kaleschke; S. Berger; S. Berger; O. Boebel; R. Drews; M. R. Ershadi; T. Fromm; F. Pattyn; D. Steinhage; O. Eisen; et al. (The Cryosphere)
Basal melting of Antarctic ice shelves significantly contributes to ice sheet mass loss, with distinct regional disparities in melt rates driven by ocean properties. In Dronning Maud Land (DML), East Antarctica, cold water predominantly fills the ice shelf cavities, resulting in generally low annual melt rates. In this study, we present a 4-year record of basal melt rates at the Ekström Ice Shelf, measured using an autonomous phase-sensitive radio-echo sounder (ApRES). Observations reveal a low mean annual melt rate of 0.44 m a−1, with a seasonal variability. Enhanced melting occurs in winter and spring, peaking at over 1 m a−1, while rates are decreased in summer and autumn. We hypothesise that the dense water formed during sea-ice formation erodes the water column stratification during late winter and spring, leading to an increase in the buoyancy of the ice shelf water plume. An idealised plume model supports this hypothesis, indicating that the plume velocity is the primary driver of seasonal basal melt rate variability, while changes in ambient water temperature play a secondary role in the range of oceanographic conditions that are observed below the Ekström Ice Shelf. These findings offer new insights into the dynamics of ice–ocean interactions in East Antarctica, emphasising the need for further observations to refine our understanding of ocean variability within ice shelf cavities and improve assessments of ice shelf mass balance.